Structural and functional aspects of liver sinusoidal endothelial cell fenestrae: a review - Braet, Filip; Wisse, Eddie (Comparative hepatology, 2002)
This review provides a detailed overview of the current state of knowledge about the ultrastructure and dynamics of liver sinusoidal endothelial fenestrae. Various aspects of liver sinusoidal endothelial fenestrae regarding their structure, origin, species specificity, dynamics and formation will be explored. In addition, the role of liver sinusoidal endothelial fenestrae in relation to lipoprotein metabolism, fibrosis and cancer will be approached.